Inclusion of flaxseed in turkey diets decreases the n‐6/n‐3 PUFA ratio and increases the proportion of biologically active EPA and DHA without affecting meat quality. Issue 6 (20th January 2015) - Jankowski, Jan; Zdunczyk, Zenon; Mikulski, Dariusz; Naczmanski, Jakub; Juskiewicz, Jerzy; Troszynska, Agnieszka; Slominski, Bogdan A.
Abstract The objective of this study was to determine the duration of diet administration required for effective modification of meat fatty acids (FA) in turkeys fed diets containing 10% of flaxseed. BIG‐7 female turkeys of 11 wk of age were randomly assigned to three dietary treatments and were fed wheat/soybean‐based diets containing 2.5% of flaxseed oil and 2% of soybean oil (FO), 10% of ground flaxseed (FS), and 10% of flaxseed and NSP‐degrading enzymes (FS + E) for 3, 4, and 5 wk. After 5 wk, the BWG of turkeys from FO and FS + E groups were similar, while group FS birds had a lower body weight (P = 0.009). When compared to the reference diet FO, diets FS and FS + E decreased (P < 0.05) the proportion of n‐6 after 4 wk, and increased the proportion of n‐3 in the total FA content of breast meat. As a result, the n‐6/n‐3 ratio for FO, FS, and FS + E decreased in breast meat (from 2.8 to 1.4, and 1.4, respectively). When compared to 4 and 5 wk, meat from turkeys slaughtered after 3 wk of feeding had lower concentrations of total n‐3 FA. However, the proportion of biologically active EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) was the highest after 3 wk. Dietary treatments did not influence the sensory attributes of breast and thigh meat evaluated after 3, 4, and 5 wk. The results indicate that administration of the diet containing 10% of flaxseed for 3 wk would improve the n‐6/n‐3 ratio and EPA and DHA contents without a negative impact on the physicochemical and sensory attributes of meat. Practical applications: The inclusion of 10% of ground flaxseed in turkey diets over a period of 3 wk before slaughter (i.e., at ∼15 wk of age) would decrease the n‐6/n‐3 PUFA ratio in meat portions and would result in considerably higher proportion of biologically active EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) without any negative impact on the physicochemical and sensory attributes of meat, and thus may be more desirable for human health. Further applications may include the use of NSP‐degrading enzymes to alleviate the negative effect of ground flaxseed on body weight gain of turkeys. <inline-graphic xlink:href="ark:/27927/pgjr0rr136" content-type="ejlt201400186-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Growing turkeys were fed wheat/soybean‐based diets containing 2.5% flaxseed oil and 2% soybean oil (FO), 10% ground flax seed (FS), and 10% ground flax seed plus NSP enzyme (FS+E) for 3, 4, and 5 wk. When compared to the reference diet FO, diets FS and FS + E increased the proportion of n‐3 in the total FA content of breast and thigh meat portions and decreased the n‐6/n‐3 ratio. Turkeys slaughtered after 3 weeks of feeding had lower concentrations of total n‐3 FA but the highest proportion of biologically active EPA and DHA.